Rodents and Zoonotic Diseases: Environmental Drivers and Prevention Measures - V. Basil Hans (International Journal of Virus Studies, 2025)
Among the most ubiquitous animal species, rats spread several human diseases. Found in cities, rural areas, and everywhere in between, rats have adapted remarkably well to living alongside people. Unfortunately, this close contact makes it easier for them to carry and pass on harmful germs. Their biology, fast breeding, and ability to host various bacteria, viruses, and parasites often without getting sick themselves make them especially effective at spreading disease.This article explores the many factors that allow rats to act as dangerous disease carriers. Some of the most serious illnesses linked to rats include hantavirus pulmonary syndrome, a severe lung infection; leptospirosis, which can lead to organ damage; plague, a disease infamous for its deadly outbreaks in history; and Lassa fever, a viral illness common in parts of West Africa. These diseases vary in how they spread and affect people, but all pose serious risks to human health.In recent years, rising urbanization, shifting climates, and environmental damage have made encounters between rats and humans more frequent. These changes have increased the chance of diseases jumping from animals to people. To tackle this growing threat, it's important to focus on prevention controlling rat populations, keeping communities clean, and educating people about how to protect themselves.Understanding rodent disease transmission is essential for designing effective therapies and lowering rodent-associated illness burdens on humans.
Keywords: Zoonotic diseases; disease transmission; epidemiology; public health; rodent control